AL-SUYŪTI DAN AL-BAHJAH AL-MARDIYYAH (Tinjauan Biografi dan Karya) - M. Pribadi (Adabiyyāt: Jurnal Bahasa dan Sastra, 2009)
Bahjah Mardiyyah, written by Jalal al-Din al-Suyuthi, is an interpretation of nazam (rhymed form) of alfiyyah Ibn Malik. It’s compactness does not make it incomplete. The discussion and the explanation, in Bahjah Mardiyyah, about intricate dictions in nazam alfiyyah Ibn Malik are quite complete. In addition, it is necessary for the students of Arabic Department to learn about it. This study uses the descriptive approach to elaborate the text in order to be able to criticize this book. With its unique patterns, this book is able to give an enlightenment of Arabic grammar. Tanbih, far’, tatimah are the methods of interpretation used in this book.